Anorexia and bulimia – perfect body versus death - Maria Aparecida Conti; Paula Costa Teixeira Costa Teixeira; Marcela S. Kotait; Eduardo Aratangy Aratangy; Fabio Salzano; Ana Carolina Soares Amaral (O Mundo da Saúde)
Nervous anorexia and nervous bulimia are food disturbances (FD) of difficult treatment and of rise morbidity. The Program of Food Disturbances (Ambulim) of IPq-FMUSP is the first multidisciplinary Brazilian center for the treatment, teaching and research of the area. The service is based on multidisciplinary actions integrating essentially medical, nutritional and psychological assistance. Physical activity is considered, since there are evidences of the association of dependence to exercise with FD. We observe a slow and gradual process leading to physical, emotional and social health worsening of a patient, with a morbid refusal to gaining weight. Her personal beliefs very often are based on the fact that “to be thin”, “stay thin” is the key for her personal, affective and social success. The expectation about the body spread in the contemporary society, characterized by a notion of perfection connected to slimness, influences the physical image, essential element the etiology of FD. The media, by their turn, offer explicit instructions about how to reach the ideal of beauty, promoting the belief that persons can, and in fact have to, to control his physical condition and weight. The work developed by a health professional with a patient who develops FD is intense and full with challenges, and must go beyond health care. It is expected that professionals could share their knowledge with the population, warning it about the risks and care modalities in order to prevent FDs to be a life style choice for young people